Case report: Extraskeletal mesenchymal chondrosarcoma with a rare metastasis to the pancreas - Zhu, Xiuliang; Cheng, Lu; Dong, Fei; Cai, Jinsong; Qian, Wei; Ding, Qiao-Ling (Frontiers in Oncology, 2024)
BackgroundExtraskeletal mesenchymal chondrosarcoma (ESMC), an uncommon and highly aggressive form of chondrosarcoma, is characterized by its mesenchymal origin and absence of skeletal involvement. Only a few cases of primary ESMC with metastasis to the pancreas have been reported so far. In this study, we present a case of ESMC in the left thigh with a solitary pancreatic metastasis in a 45-year-old woman. Additionally, we provide a thorough overview of ESMC, encompassing its entire clinical progression and radiographic observations. Furthermore, we reviewed all thirteen cases of pancreatic metastasis, including this present case, analyzing patient attributes, clinical management, and prognosis.Case presentationA 45-year-old woman has had a painless mass in her left thigh for one year. X-ray, computed tomography (CT), and magnetic resonance imaging of the left thigh were performed. Positron emission tomography-CT imaging showed a high accumulation in the left thigh tumor and the pancreatic neck lesion. A diagnosis of extraskeletal chondrosarcoma with pancreatic metastasis was determined based on the radiological examinations. A final diagnosis of ESMC was confirmed by histopathological and immunohistochemical examinations after surgical resection. The patient presented metastasis in the lung, right groin, and tail of the pancreas successively, and mostly received complete surgical excision during a 39-month follow-up with postoperative chemotherapy.ConclusionWe present a highly uncommon case of ESMC spreading to the pancreas and highlight the importance of recognizing the distinctive imaging features of ESMC for diagnosis and prognosis assessment.